NiCo-sulfide hetero-structured interface induced highly active nickel-dominated metal sites for oxygen evolution reaction. (12th June 2022) - Hou, Jingting; Yuan, Meichen; Grigoriev, Sergey A.; Yang, Zehui; Lai, Qingxue; Liang, Yanyu
Abstract: The development of sustainable energy is of great significance for relieving the energy shortage crisis, where the oxygen evolution reaction (OER) in water electrolysis plays a crucial role in efficient energy conversion technology. Hetero-structured transition metal sulfides are regarded as quite promising electrocatalytic materials, considering their intrinsic activity and prominent synergistic effect. However, the essential surface reconstruction process of transition metal sulfides renders a great challenge to reveal the real active sites and the relative electrocatalytic reaction mechanism. Herein, novel sea urchin-like NiCo bimetallic sulfide (denoted as NiS/Co3 S4 ) catalysts with highly exposed heterogeneous interface is designed for efficient OER. The high electrochemical active surface as well as effectual charge-transfer effect ensures NiS/Co3 S4 catalysts with superior activity and durability, such as a low overpotential of 285 mV at 100 mA/cm 2, a small Tafel slope of 66 mV/dec as well as the long-term stability for 60 h. The post OER characterizations confirm that high valence of Ni dominated metal sites expedite the surface reconstruction process and the formed Ni (oxy)hydroxides significantly accelerate the process of oxygen evolution reaction. Graphical abstract: Image 1 Highlights: The sea-urchin like NiS/Co3 S4 catalysts with high electrocatalytic performance. Prominent charge-transfer effect led to highly active nickel-dominated metal sites. Ni (oxy)hydroxides were identified as the major active species.